La eficiencia del gasto público en la municipalidad provincial de Chiclayo y su impacto socio económico en el periodo 2007-2009- - Olivos Campos, Carlos Alberto (2019)
ABSTRACT The present investigation was carried out, given that the management of the City Council of Chiclayo maintains a subsisting concern about the management of public funds and the scarce concretions in works of great social impact, and also because despite the improvements in administration, the financial situation of the municipal government is perceived to be far from achieving more works and therefore better services to the community. For the study, the population and the sample, - non-probabilistic sample and convenience - was made up of the universe composed of all officials and administrative employees who work in the Provincial Municipality of Chiclayo, therefor a survey on variables, education and culture was formulated, sanitation and health, transportation. Likewise, a perception survey was taken of 130 residents or residents of Chiclayo, about the benefits and impact of the public works carried out in Chiclayo in the 2007-2009 period. To carry out the analysis of the management of the Provincial Municipal Council of Chiclayo, the municipal budgets, the local expenditure were taken into account and a comparison was made of the measurement of the efficiency of their peers at the national level. In this regard, it is concluded that the municipal management of the province of Chiclayo has not had an efficient use of budgetary resources in the 2007-2009 period. The results obtained, highlight the need to concentrate greater efforts in improving the efficiency of spending at the level of the province of Chiclayo.